The Effect Of Recruitment, Selection, And Placement Of Work Positions On Employee Performance - Melly Nindiya; Ibnu Haris Nasution (SEAN Institute, 2023)
The purpose of this study is to determine the effect of recruitment, selection and job placement on employee performance. This study uses quantitative research methods with data collection techniques through questionnaires and supported by secondary data. The data analysis method used is multiple linear regression analysis. The number of samples is 102 respondents from employees of PT Mitra Karsa Utama.The results of this study partially show that the recruitment variable has no positive and significant effect on employee performance at PT Mitra Karsa Utama. Partially, the selection variable has no positive and significant effect on the performance of employees of PT Mitra Karsa Utama. Partially the placement variable has a positive and significant influence on the performance of employees of PT Mitra Karsa Utama. And simultaneously recruitment, selection, to placement shows an influence on employee performance.